Pengkayaan Artemia dengan Berbagai Dosis Bawang Putih Terhadap Pertumbuhan dan Sintasan Pasca Larva Udang Vaname - Dafi, Andi; Malik, Andi Adam (Integrated and Sustainable Agriculture, 2024)
This study evaluates the effect of Artemia enrichment with garlic (Allium sativum) on the growth and survival of vannamei shrimp (Litopenaeus vannamei) post-larvae. Using a completely randomized design (CRD), four garlic enrichment doses were tested: 0 ppm (control), 250 ppm, 500 ppm, and 750 ppm, with three replicates each. Results showed no significant effect on larval growth, with the highest length recorded at 11.5 mm. However, survival increased significantly, reaching 88.28% at 750 ppm. Allicin in garlic likely acts as a natural immunostimulant, enhancing larval resistance to stress and infection. The optimal dose for Artemia enrichment is 750 ppm. This study highlights garlic’s potential as a natural ingredient to improve vannamei shrimp hatchery practices.